Exploring the Relationship between Podcast Engagement and Selective Listening Skills among EFL Learners - Siti Ananda Zalzabila Mudjarab; Nabila Syahrani; Nella Yuadiah Ningsih; La Sunra (Universitas Islam Negeri Palopo, 2026)
This study explores the relationship between podcast engagement and selective listening abilities in EFL learners. Although podcasts have become increasingly popular in language learning, limited research has examined the relationship between learners' engagement with podcasts and their selective listening abilities, particularly among EFL students in Indonesian universities. This study addresses this gap by investigating the relationship between podcast engagement, encompassing behavioral, cognitive, and emotional dimensions, and learners' selective listening abilities. The findings provide practical implications for EFL educators, highlighting the importance of integrating podcast-based activities into language instruction to foster active listening and enhance information-processing skills. The study employed a quantitative correlational design and included 30 English Education students from UIN Alauddin Makassar. Data collection involved administering a Selective Listening Test alongside a Podcast Engagement Questionnaire. The analysis using Pearson correlation demonstrated a robust and statistically significant relationship between podcast engagement and selective listening skills (r = 0.890; p < 0.01). The results suggest that increased interaction with podcasts correlates with an enhanced capacity to discern essential information and understand spoken content proficiently. The findings indicate that podcasts function as a valuable authentic learning tool for improving listening skills, especially in the area of selective listening. It is advisable for upcoming studies to incorporate larger sample sizes and mixed-method strategies to enhance the comprehension of learners’ engagement patterns.